Teachers’ Perceptions towards National Programme of Nutritional Support to Primary Education (Mid-Day Meal Scheme) - Kumar, Anup (THE PRIMARY TEACHER, 2008)
This study was conducted in Government Primary Schools of Mandi district of Himachal Pradesh to find out preceptions of primary school teachers about the National Programme of Nutritional Support to Primary Education (Mid-Day Meal Scheme). A sample of 70 teachers, which included both males and females, were selected using purposive sampling technique. In the present study teachers’ preceptions were studied by using a questionnaire. Along with this various problems related to implementation of this scheme were identified and suggestions were provided for making the scheme more effective. This study will be very helpful to the politicians, bureaucrats, researches, teachers and all others who are concerned with the mission to develop elementary education and reach the goal of UEE in India.